TRADISI LISAN BALAWAS SUMBAWA: REPRESENTASI ISLAM SEBAGAI DOA KESELAMATAN - muhammad saleh (Penamas, 2019)
Balawas (religious folk poetry) is one of the Indonesian Islam oral poetry traditions, widely performed in Muslim community across the archipelago. Although studies on Balawas have garnered great attention, little attention has been given to the study of Balawas Akherat called Pamuji, which is practiced widely by Sumbawanese community. To fill this void, this ethnographic study aims to explore the practices of Sumbawanese Balawas Akherat, particularly the forms of the texts and how they were perceived by the Sumbawanese community.The data were collected through observation, in-depth interview, and documentation. The empirical evidence showed that arabic symbols are replaced by local symbols, another finding also unveiled that the oral poetry tradition of Sumbawanese was perceived as prayers that can bring salvation.